In vivo tumour extracellular pH monitoring using electron paramagnetic resonance: the effect of X‐ray irradiation. (28th January 2014) - Goodwin, Jonathan; Yachi, Katsuya; Nagane, Masaki; Yasui, Hironobu; Miyake, Yusuke; Inanami, Osamu; Bobko, Andrey A.; Khramtsov, Valery V.; Hirata, Hiroshi
<x xml:space="preserve">Abstract</x> The in vivo quantification of extracellular pH (pHe) in tumours may provide a useful biomarker for tumour cell metabolism. In this study, we assessed the viability of continuous‐wave electron paramagnetic resonance (CW‐EPR) spectroscopy with a pH‐sensitive nitroxide for the measurement of extracellular tumour pH in a mouse model. CW‐EPR spectroscopy (750 MHz) of C3H HeJ mice hind leg squamous cell tumour was performed after intravenous tail vein injection of pH‐sensitive nitroxide (R‐SG, 2‐(4‐((2‐(4‐amino‐4‐carboxybutanamido)‐3‐(carboxymethylamino)‐3‐oxoproylthio)methyl)phenyl)‐4‐pyrrolidino‐2, 5, 5‐triethyl‐2, 5‐dihydro‐1Н‐imidazol‐1‐oxyl) during stages of normal tumour growth and in response to a single 10‐Gy dose of X‐ray irradiation. An inverse relationship was observed between tumour volume and pHe value, whereby, during normal tumour growth, a constant reduction in pHe was observed. This relationship was disrupted by X‐ray irradiation and, from 2–3 days post‐exposure, a transitory increase in pHe was observed. In this study, we demonstrated the viability of CW‐EPR spectroscopy using R‐SG nitroxide to obtain high‐sensitivity pH measurements in a mouse tumour model with an accuracy of <0.1 pH units. In addition, the measured changes in pHe in response to X‐ray irradiation suggest that this may offer a useful method for the assessment of the physiological change in response to existing and novel cancer therapies. Copyright © 2014 John Wiley & Sons, Ltd.